2016
DOI: 10.1249/mss.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exercise on Visceral Adipose Tissue in Older South Asian Women

Abstract: In intention-to-treat analysis VAT was not significantly reduced after 12 wk of either standard or culturally based exercise. However, attendance in both standard and culturally based exercise was high, and VAT was significantly reduced among SA women who adhered to these programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…The following results are a sub analysis of the data from the previously published randomized controlled trial from which this population was contrived. We have previously found in within-group pre-post comparisons, that there was a significant reduction in VAT (p=0.040) and WC (p=0.037) after a 12-week standard exercise program, as well as in SAAT (p<0.001), TAAT (P<0.001), BMI (p=0.027), WC (p<0.001), body fat (p=0.036) and glucose (p=0.039) after a 12-week Bhangra dance program (Lesser et al, 2016).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The following results are a sub analysis of the data from the previously published randomized controlled trial from which this population was contrived. We have previously found in within-group pre-post comparisons, that there was a significant reduction in VAT (p=0.040) and WC (p=0.037) after a 12-week standard exercise program, as well as in SAAT (p<0.001), TAAT (P<0.001), BMI (p=0.027), WC (p<0.001), body fat (p=0.036) and glucose (p=0.039) after a 12-week Bhangra dance program (Lesser et al, 2016).…”
Section: Resultsmentioning
confidence: 93%
“…We have previously found in within-group pre-post comparisons, that there was a significant reduction in VAT (p=0.040) and WC (p=0.037) after a 12-week standard exercise program, as well as in SAAT (p<0.001), TAAT (P<0.001), BMI (p=0.027), WC (p<0.001), body fat (p=0.036) and glucose (p=0.039) after a 12-week Bhangra dance program (Lesser et al, 2016). Therefore, our primary objective in this study was to assess the associations between changes in VAT, SAAT, WC, percent body fat and BMI with changes in cardiometabolic risk factors following a 12-week supervised aerobic exercise intervention in inactive, post-menopausal South Asian women as a follow-up to the above mentioned randomized controlled trial.…”
Section: Introductionmentioning
confidence: 93%
“…Numerous studies of various forms of physical activity have been conducted in a range of populations. In randomised trials, exercise interventions have demonstrated improvements in one or more of the components of MetS in South Asians [72][73][74] and East Asians [75,76]. In Chinese men, an intervention of Tai Chi was effective at reducing BP and TG [77].…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…For example, South Asians have lower physical activity levels compared with other populations [132,133], which may be rooted in cultural context [134]. In addition, adherence to and enjoyment of exercise may be based on the physical activity type, which also may have cultural relevance, such as Bhangra dance in South Asians [73] or Tai Chi in East Asians [135].…”
Section: Other Considerationsmentioning
confidence: 99%
“…Indeed, a number of studies conducted in Canada showed the positive impact PA has on the SACs population in reducing CVD risk factors (Table 1 ) and their predictors. For example, Lesser et al showed that a 12-weeks PA intervention significantly reduced total abdominal adipose tissue, visceral adipose tissue (VAT), subcutaneous abdominal adipose tissue, waist circumference (WC), and body fat percentage amongst SACs ( 29 , 30 ). They also found an overall improvement in aerobic fitness, and an association between changes in VAT and changes in glucose and insulin sensitivity.…”
Section: Physical Activity Interventions For Cvd Prevention In Sacsmentioning
confidence: 99%